KARAKTERISTIK PATI BERPORI MIKRO DARI TAPIOKA HASIL PERLAKUAN AMILASE SEBAGAI AGEN PENJERAPAN MINYAK [The Characteristic of Microporous Tapioca Starch After Amylase Treatment For Oil Adsorbent Agent] - Dwi Ajias Pramasari; Dewi Sondari; Danang Sudarwoko Adi; Bernadeta Ayu Widyaningrum; Anugerah Fajar; Rahmawati Putri; Witta Kartika Restu; Eka Hapsari Putri (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2020)
Microporous starch can be used as oil adsorbent agent. The microporous starch can be produced through partial hydrolysis at temperature below gelatinization point using amylase. On the other hand, the study of amylase produced from Indonesian sea microbe, especially Brevibacterium sp. was rarely studied. Therefore, this paper discusses the tapioca characteristic made from Brevibacterium sp. amylase (treatment A) and commercial amylase (treatment B) as oil adsorbent agent. The result showed that the yield from treatment A and B was 74.65% and 12.75% while the starch granule size was 14.60 μm and 12,59 μm. The adsorbent test showed adsorption level of oil palm were 91,08% and 142,14% while for olive oil were 94,70% and 133,17%, for treatment A and B, respectively. The morphological test showed the presence of pori on the granule surface for both treatments with FTIR assessment showed no significant change in chemical functional group for both treatments. The color analysis showed almost similar brightness level between two treatments. In the end, microporous starch of treatment A has prospect as oil adsorbent agent like the one from commercial amylase